Hydrogen Applications and Solid-State Storage Materials: A Critical Review of Mechanisms, Material Innovations, and Prospects Toward Practical Hydrogen Energy Systems - Amelia, Icha; Rohendi, Dedi; Nurcholifah, Yollanda (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2026)
Hydrogen has significant potential as a clean energy carrier to support the transition toward sustainable energy systems. However, the widespread implementation of a hydrogen economy is still limited by challenges associated with safe, efficient, and high-capacity hydrogen storage technologies. In general, hydrogen storage systems are classified into physical storage, chemical storage, and solid-state storage. This review article systematically discusses various hydrogen storage technologies, with a particular focus on solid-state hydrogen storage, including metal hydrides, complex hydrides such as alanates, and chemical hydrides encompassing borohydrides and liquid organic hydrides. Each class of materials is evaluated in terms of storage capacity, thermodynamic and kinetic characteristics, as well as issues related to reversibility and regeneration. The review highlights that, despite considerable progress, no single hydrogen storage system currently satisfies all practical requirements. Therefore, a fundamental understanding of hydrogen–material interactions, along with material design and catalytic strategies, is essential for advancing hydrogen storage technologies toward practical applications.Keywords: Hydrogen storage; Solid-state hydrogen storage; Metal hydrides; Chemical hydrides; Thermodynamic and kinetic properties